Solid state and aqueous solution characterization of rectangular tetranuclear VIV/V-p-semiquinonate/hydroquinonate complexes exhibiting a proton induced electron transfer - Keramidas, Anastasios D.; Drouza, Chryssoula (My University, 2008)
Reaction of the non-innocent dinucleating ligand 2,5-bis[N,N- bis(carboxymethyl) arninomethyl]hydroquinone (H6bicah) with VO 2+ and VO43- salts in water in the pH range 2 to 4.5 provides a series of novel tetranuclear VIV and/or V V macrocycles with the main core consisting of the anions [V V4O4(a-0)2(μ-bicah)2] 4- isolated at pH = 2.5 and [VIV2V V2O4(μ-O)2(μ-bicas)(μ- bicah)]5- and [VIV4O4(μ-O) 2(μ-bicas)2]6- isolated at pH = 4.5 (bicas•5- = 2,5-bis[N,N-bis(carboxymethyl) aminomethyl]-p- semiquinonate), whereas at pH = 2 the dinuclear [(VIVO) 2(OH2)2(μ-bicah)]2- was obtained. All vanadium compounds have been characterized, and the charge of the ligand has been assigned in solid state by X-ray crystallography and infrared spectroscopy. The structures of the tetranuclear anions consist of four vanadium atoms arranged at the corners of a rectangle with the two bridging bicas •5- and/or bicah6- ligands on the long and the two VIV/V-O-VIV/V bridges on the short sides of the rectangle. UV-vis, 51V and 1H NMR spectroscopy and electrochemistry showed that these complexes interconvert to each other by varying the pH. This pH induced redox transformation of the tetranuclear anions has been attributed to the shift of the reduction potential of the bicas•5- to higher values by decreasing the pH. The electron is transferred intramolecularly from the metal ion to the electron accepting semiquinones resulting in reduction of bicas•5- to bicah6- and concurrent oxidation of the VIV to VV. The resulting complexes are further oxidized by atmospheric oxygen. This system as a model for the H + coupled redox reactions in metalloenzymes and its relevance is discussed briefly
Keywords: Hydroquinone; organometallic compounds; Vanadium; Water; Chemistry; Electrochemistry; Electron transport; Magnetism; X-ray crystallography